Knowledge management as a strategic innovation tool in organizations. An integrative review - Rodrigues Koller, Elaine (2024)
The article investigates Knowledge Management (KM) as a strategic tool to foster innovation within organizations. The study focuses on how KM can be used to enhance competitiveness and organizational effectiveness through innovation. Using an integrative review methodology, the research identified 13 main categories of investigation in the current literature, highlighting the interrelationship between KM and various organizational aspects such as competitiveness, strategy, innovation, and learning. The central problem of the study questions how KM has been applied as a strategic tool for effective innovation management, while the general objective is to analyze the role of KM in promoting innovation within organizations, aiming to achieve competitive advantages and better market positioning. The research was conducted through an integrative review, analyzing various academic publications to assess how KM is approached in terms of strategic innovation. The publication excerpts range from 1990 to 2023, selected based on their relevance to knowledge management and innovation. The results indicate that organizations focused on KM achieve better innovation outcomes, directly impacting their performance. The findings emphasize the need for strategic knowledge management to promote continuous innovation. The study contributes to the understanding and integration of KM as a catalyst for innovation and organizational strategy, creating an environment conducive to the development of new ideas and continuous improvements.